Gender and Learning Styles: A Correlational Study of Preferences Among English Education Students in Universities - Ananda Sri Wahyuni; Hani, Hani; Nunung Nurjanah; Nastiar Maulida Utami; Lystiana Nurhayat Hakim (Journal of Applied Linguistics (ALTICS), 2025)
Understanding learning style preferences is essential for educators and institutions in designing strategies for instruction and improving student learning results. The purpose of this study is to find out whether there is a relationship between gender and learning style preferences among English Education students using a quantitative approach and a correlational study design. A VARK model-based online questionnaire was used to collect data from 50 students recruited by snowball sampling. Descriptive analysis showed that there was highly dominant learning style among the students. The t-test showed no significant difference in male and female learning style preferences. Pearson correlation research showed no significant association between gender and learning style preference. However, a strong and significant correlation was found between the four learning styles. The questionnaire's reliability was high, with Cronbach's Alpha values ranging from 0.868 to 0.946. This study concludes that gender has no significant influence on the learning style preferences of English Education students, indicating the importance of using a variety of teaching approaches to accommodate students' various learning preferences.